(untitled) (Research, Society and Development, 2021)
Objective: Analyzing studies related to Adverse Drug Events (ADE) in hospitalized patients in Brazil. Method: integrative review, for which the National Library of Medicine (PubMed), Biblioteca Virtual de Saúde (BVS), Repository of the Fundação Oswaldo Cruz (FIOCRUZ) and Capes Journals databases were selected for searching the studies primary, with the descriptors: Patient Safety, Drug-related side effects and adverse reactions, Patient harm, Hospitalization, Inpatients. Results: Twenty articles were identified, 50% (10) were from the southeast region of Brazil. Regarding the methodology adopted to identify the ADEs, 70% (14) used the retrospective data review. The trackers were used in 5 (25%) articles, 3 of which used the triggers proposed by the Institute for Healthcare Improvement, and the other 2 the trackers used were proposed by the researchers themselves. The number of adverse drug reactions ranged from 12 to 96, while the occurrence of AE ranged from 4 to 122. In one study 50% (41) of participants had at least one adverse drug event. Conclusion: There is great variability in scientific production in Brazil, and in the occurrence of Adverse Drug Events as well. There is a need for strategies to identify these events and create strategies to promote patient safety.